2001
DOI: 10.1161/hh2001.097797
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Reversal of the Diabetic Endothelial Dysfunction by Pharmacological Inhibition of Poly(ADP-Ribose) Polymerase

Abstract: Abstract-Oxygen-and nitrogen-derived free radicals and oxidants play an important role in the pathogenesis of diabetic endothelial dysfunction. Recently we proposed the importance of oxidant-induced DNA strand breakage and activation of the nuclear enzyme poly(ADP-ribose) polymerase (PARP) in the pathogenesis of diabetic endothelial dysfunction.In this study, we tested whether established diabetic endothelial dysfunction is reversible by PARP inhibition. The novel PARP inhibitor PJ34 (10 mg/kg per day PO) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
186
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(194 citation statements)
references
References 49 publications
8
186
0
Order By: Relevance
“…To ensure that our findings were not specific to the C57BL/6 strain, we carried out similar experiments in Balb/c mice. Diabetes was induced by peritoneal injection of STZ (Sigma-Aldrich, Gillingham, UK), 200 mg/kg for Balb/c and 160 mg/kg for C57BL/6 and GCH-Tg, or of STZ vehicle (citrate buffer; control), as previously described [22][23][24]. Blood glucose was monitored weekly using a one-touch blood glucose meter (Lifescan, High Wycombe, UK); body weight was also measured weekly.…”
Section: Methodsmentioning
confidence: 99%
“…To ensure that our findings were not specific to the C57BL/6 strain, we carried out similar experiments in Balb/c mice. Diabetes was induced by peritoneal injection of STZ (Sigma-Aldrich, Gillingham, UK), 200 mg/kg for Balb/c and 160 mg/kg for C57BL/6 and GCH-Tg, or of STZ vehicle (citrate buffer; control), as previously described [22][23][24]. Blood glucose was monitored weekly using a one-touch blood glucose meter (Lifescan, High Wycombe, UK); body weight was also measured weekly.…”
Section: Methodsmentioning
confidence: 99%
“…This concept has been supported by research showing nitrotyrosine formation in the plasma of diabetic patients (Ceriello et al, 2001). Elevated nitrotyrosine levels have also been observed in blood vessels and retinas from diabetic rats (El-Remessy, 2003b;ElRemessy et al, 2006;Kowluru, 2003;Kowluru and Koppolu, 2002;Soriano et al, 2001). Moreover, exogenous peroxynitrite increases VEGF expression in cultured RECs (Platt et al, 2005).…”
Section: 74mentioning
confidence: 98%
“…Activation of PARP and beneficial effects of various PARP inhibitors have been demonstrated in various forms of endothelial dysfunction such as the one associated with circulatory shock, hypertension, atherosclerosis, preeclampsia and aging (Szabó et al 1997, Hung et al 2002, Martinet et al 2002. Furthermore, recent data suggest that activation of PARP importantly contributes to the development of endothelial dysfunction in various experimental models of diabetes and also in humans (Garcia Soriano et al 2001, Soriano et al 2001a, Pacher et al 2002d, Szabó et al 2002b). In addition, it has recently been demonstrated that PARP activation plays a pathogenetic role in diabetic nephropathy, neuropathy and retinopathy , Minchenko et al 2003, Li et al 2004.…”
Section: Poly(adp-ribose) Polymerase and Its Activationmentioning
confidence: 99%